The Impact of Climatic Characteristics on the Soil of the Islands of Sindbad and Um Al-Rusas - Abd Ali Shanan, Researcher. Khadija; Abdullah Rahim, Prof. Dr. Najem (Basra studies journal, 2024)
This study investigates the influence of climatic conditions on soil properties in the study area. Climate is a crucial natural factor affecting soil formation, including its physical and chemical attributes. The study examines solar radiation, temperatures, wind patterns, rainfall, relative humidity, and evaporation rates. Findings indicate that the study area experiences prolonged periods of above-average temperatures for over six months due to intense solar radiation perpendicular to the Tropic of Cancer. The region is also influenced by tropical air masses, resulting in extended daylight hours and clear skies. Moreover, wind speed significantly impacts soil properties, particularly during dry months. Increased wind speeds enhance surface evaporation and the drying of adjacent moist air layers, leading to desiccation and disaggregation of the non-vegetated soil surface. Rainfall exhibits seasonal variability, with concentrations during winter and reduced amounts in summer.